MAKER CULTURE AT CURIAR XP: SUSTAINABILITY IN THE PRODUCTION OF CAZUMBÁ IN SÃO JOSÉ DE RIBAMAR (VERUM: Journal of Scientific Initiation, 2026)
During the July 2025 school break, the Curiar XP program, promoted by the Municipal Education Department of São José de Ribamar/MA, took place. The program offers educational and cultural experiences to students, focusing on their holistic development. In this context, an Art Workshop based on Maker Culture was developed to stimulate creativity, collaboration, and student leadership in a playful, participatory, and collectively constructed environment, guided by the principle of "learning by doing." The Cazumbá, a mystical figure related to the origin of the Bumba-meu-boi in Maranhão, is part of the Baixada accent and represents an important element of local cultural identity. Thus, proposing pedagogical activities based on Maker Culture means valuing the culture to which the students belong, promoting the recognition of their roots. The workshop, inspired by the representation of the Cazumbá, enabled the exchange of experiences, the strengthening of cultural appreciation, and the development of ecological awareness by using sustainable and accessible materials, making learning more meaningful and contextualized.
Keywords: Maker Culture; Cazumbás; Sustainable Education; Curiar XP